Phasic and Tonic Locus Coeruleus Stimulation Associated Valence Learning Engages Distinct Adrenoceptors in the Rat Basolateral Amygdala - Omoluabi, Tamunotonye; Power, Kyron D.; Sepahvand, Tayebeh; Yuan, Qi (Frontiers in Cellular Neuroscience, 2022)
Reward exploitation and aversion are mediated in part by the locus coeruleus (LC), a brainstem structure significantly involved in learning and memory via the release of norepinephrine. Different LC firing patterns are associated with different functions. Previously, we have shown that high tonic and phasic LC activation signal negative and positive valence respectively, via basolateral amygdala (BLA) circuitry. Tonic LC activation is associated preferentially with BLA-central amygdala (CeA) activation, while phasic LC stimulation preferentially recruits the BLA-nucleus accumbens (NAc) pathway. Here, we ask if phasic and tonic LC activation-associated valence learning requires different adrenoceptors in the BLA, in comparison with the odor valence learning induced by natural reward and aversive conditioning. Using optogenetic activation of the LC and local drug infusions in the BLA, we show that phasic LC activation-induced positive odor valence learning is dependent on both α1 and β-adrenoceptors, whereas tonic LC activation induced negative odor valence learning via β-adrenoceptors only. The same adrenoceptor requirements were found in the odor valence learning induced by reward and aversive conditioning respectively. Phasic stimulation and reward conditioning likewise activated more NAc-projectors of the BLA, in comparison to the tonic and aversive conditioning. There was a higher portion of α1+ cells in the NAc projectors compared to CeA projectors in the BLA. Together, these results provide insight into the mechanisms underlying the effects of tonic and phasic activation of the LC, and more generally, negative and positive valence signaling.